Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1139/h00-007
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory Threshold and Maximal Oxygen Uptake in Present Triathletes

Abstract: The aim of this study was to determine the physiological profile of young triathletes who began triathlon competition as their first sport. Twenty-nine male competitive triathletes (23 regionally and nationally ranked triathletes and 6 elite, internationally ranked triathletes) performed two tests, one on a cycle ergometer (CE VO2max) and one on a treadmill (TM VO2max). Results showed (a) no difference between CE VO2max and TM VO2max in the triathletes (69.1 +/- 7.2 vs. 70.2 +/- 6.2 mL x kg(-1) x min(-1), resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
2
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 27 publications
8
44
2
2
Order By: Relevance
“…Our group demonstrated that incremental cycling and running _ V V O 2max were similar in young triathletes without prior athletic specialization (Hue et al 2000b), which was the case of the present subjects. The cycling _ V V O 2max value was thus used to express both the running and cycling intensities in terms of % of _ V V O 2max during trials 1 and 2.…”
Section: Testing Protocolsupporting
confidence: 80%
“…Our group demonstrated that incremental cycling and running _ V V O 2max were similar in young triathletes without prior athletic specialization (Hue et al 2000b), which was the case of the present subjects. The cycling _ V V O 2max value was thus used to express both the running and cycling intensities in terms of % of _ V V O 2max during trials 1 and 2.…”
Section: Testing Protocolsupporting
confidence: 80%
“…] as gross criterion of endurance performance was slightly lower than that reported by Hue, Le Gallais, Chollet, and Préfaut (2000) and Schabort et al (2000), and similar to that reported by Hue (2003). Lactate values could not be compared because of various specifications such as defined bounds, running paces, or power outputs while cycling.…”
Section: Assessment Of Parameterssupporting
confidence: 47%
“…For future performance prediction by means of motor tests, studies usually suggest laboratory tests for the sake of objectivity of data gained (OʼToole, Douglas, & Hiller, 1989;Neumann, 1993;Hue, Le Gallais, Chollet, Boussana, & Préfaut, 2000;Bentley, Millet, Vleck, & McNaugthon, 2002). The most commonly used is a treadmill or cycling ergometer test up to vita maximum, further speed tests at AT, less on aerobic threshold (Schabort, Killian, St Clair Gibson, Hawley, & Noakes, 2000;Hue, 2003;Van Schuylenbergh, Vanden Eynde, & Hespel, 2004).…”
Section: Methodology Of Talent Selection For Short Triathlonmentioning
confidence: 99%